THE ROLE OF PARASTERNAL MEDIASTINOTOMY IN THE DIAGNOSIS OF MEDIASTINAL TUMORS - O. V. Pikin; A. B. Ryabov; A. O. Alexandrov; D. A. Vursol; A. M. Amiraliev (Исследования и практика в медицине)
Parasternal mediastinotomy is a surgical method of morphological verification of mediastinal tumors, widely performed in oncological clinics. The article provides information about the method of implementation and the results of parasternal mediastinotomy for malignant tumors of the mediastinum.Purpose of the study. Evaluation of the results of parasternal mediastinotomy for morphological verification of mediastinal tumors.Patients and methods. The study included 77 patients who for the period from 2008 to 2018. 80 parasternal mediastinotomies were performed with a biopsy of a mediastinal tumor in the conditions of the Department of Thoracic Surgery of the P. Hertsen Moscow Oncology Research Institute. At the stage of preoperative examination, all patients underwent standard diagnostic studies: computed tomography of the chest, abdominal cavity, and a comprehensive ultrasound. In the case of the presence of the endobronchial component of the tumor, fibrobronchoscopy was performed. MRI of the brain was performed in patients with neurological symptoms. 12-lead ECG, echocardiography, and a study of the function of external respiration were performed to assess the functional status of patients.Results. The final histological diagnosis was made in 76 of 77 (99%) patients. The clinical diagnosis of lymphoma was set in 66, thymoma — in 6 patients, lung cancer with affection of mediastinal lymph nodes — in 4 patients, mediastinal tumor — in 4 patients. In 24 patients (31%), operations were preceded by other attempts at morphological verification. In 12 patients — mediastinal tumor biopsy under ultrasound control, in 3 — parasternal mediastinotomy, in 2 — transthoracic mediastinal tumor biopsy combined with biopsy of supraclavicular lymph node under ultrasound control, 2 — biopsy of supraclavicular lymph node under ultrasound control, in 1 — mediastinum tumor biopsy under control. — chest wall biopsy, in 1 — open biopsy with thoracotomic access, in 1 — tonsil biopsy, in 1 — trachea biopsy. In all cases, the indication for performing a parasternal mediastinotomy was an insufficient amount of material for carrying out a complete immunohistochemical study.Conclusion. Parasternal mediastinotomy is a safe and reliable method of morphological verification of the formations of the anterior mediastinum and para-aortic region. In case of the ineffectiveness of transthoracic biopsy under the control of ultrasound or CT navigation, the performing of parasternal mediastinotomy allows to establish a morphological diagnosis and to begin a specific treatment in the shortest possible time.